Quietly Loud: Unearthing Aversive Racism in Angie Thomas’s The Hate U Give - Radma Gul; Saima Ayaz; Laila (University of Chitral Journal of Linguistics and Literature, 2024)
The current study explores a fairly unnoticeable but rampant kind of racism known as aversive racism, identified by Samuel L. Gaertner and John F. Dovidio; in Angie Thomas’s sensational work The Hate U Give. It illuminates the way different characters in the novel are racists without meaning to be and how racism only exists in their subconscious of which they are ignorant. They consciously believe in the equality of all races. The present study is a dive into the psyche of the aversively racist characters and analyzes how their subconscious racist beliefs shape their behavior. It divulges the different ways aversive racism is practiced and how Black people and other minorities suffer because of it as depicted in the novel. The research contributes to creating awareness regarding this detrimental racism and its pernicious effects in society, like how it stimulates interracial mistrust and resentment among the Black and White races; and how it may be inhibited. The critical analysis of the novel also yields that aversive racism could very well be the major cause of the spontaneous killing of Black people at the hands of White cops. It also elucidates how society remains divided and broken because of these racial issues presented in the novel. The entire system in America being aversive racist is also unveiled through a thorough dissection of the book.